2017
DOI: 10.1259/bjr.20160594
|View full text |Cite
|
Sign up to set email alerts
|

Microcalcification on mammography: approaches to interpretation and biopsy

Abstract: This article discusses the significance of microcalcifications on mammography and the changes in technology that have influenced management; it also describes a pragmatic approach to investigation of microcalcification in a UK screening programme. BACKGROUND AND PREVALENCE OF MICROCALCIFICATIONSMicrocalcifications result from the deposition of calcium oxalate and calcium phosphate within the breast tissue. The mechanism by which calcium deposition occurs is not clearly understood; it may be an active cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 35 publications
(25 reference statements)
0
60
0
2
Order By: Relevance
“…It has been shown that the presence of suspicious clustered microcalcifications on a negative screening is important for short‐term risk prediction . However, It has been suggested that even nonsuspicious microcalcifications are associated with breast cancer . To understand more about the role of microcalcifications in short‐term risk of breast cancer, large‐scale epidemiology studies need to be carried out and these will likely require the availability of algorithms for detecting microcalcifications on for‐presentation mammographic images.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the presence of suspicious clustered microcalcifications on a negative screening is important for short‐term risk prediction . However, It has been suggested that even nonsuspicious microcalcifications are associated with breast cancer . To understand more about the role of microcalcifications in short‐term risk of breast cancer, large‐scale epidemiology studies need to be carried out and these will likely require the availability of algorithms for detecting microcalcifications on for‐presentation mammographic images.…”
Section: Introductionmentioning
confidence: 99%
“…This had been partly explored long back, where the osteotropism of breast cancer was correlated with its ability of inducing microcalcifications by expressing bone matrix proteins (78). Clinically, mammographic calcifications aid in distinguishing benign from potentially malignant changes (79). Although calcium oxalate is mostly associated with benign tumors, hydroxyapatite has been linked to both benign and malignant ones (80).…”
Section: Bone Metastasismentioning
confidence: 99%
“…The detection of minerals in breast tissue is key to the early diagnosis of breast cancer 3,9,10 . Breast screenings are widely used to examine for the presence of calcifications, which are, in many cases, the only detectable sign of a tumour 11 .…”
Section: Of Tumour Tissue But Also Enable a Precise Yet Simple Routmentioning
confidence: 99%